2020
DOI: 10.1007/s13753-020-00282-x
|View full text |Cite
|
Sign up to set email alerts
|

Modified Usability Framework for Disaster Apps: A Qualitative Thematic Analysis of User Reviews

Abstract: The public has access to a range of mobile applications (apps) for disasters. However, there has been limited academic research conducted on disaster apps and how the public perceives their usability. This study explores end-users’ perceptions of the usability of disaster apps. It proposes a conceptual framework based on insights gathered from thematically analyzing online reviews. The study identifies new usability concerns particular to disaster apps’ use: (1) content relevance depends on the app’s purpose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…The social vulnerability evaluation concentrates on features of potential weaknesses capacities of the human population (Tan et al 2020…”
Section: Social Vulnerabilitymentioning
confidence: 99%
“…The social vulnerability evaluation concentrates on features of potential weaknesses capacities of the human population (Tan et al 2020…”
Section: Social Vulnerabilitymentioning
confidence: 99%
“…IoT devices can be unreliable because they are enormously taxing on network bandwidth (Celic and Magjarevic, 2020; Nicolescu et al, 2018). Emergency and natural disaster notifications often come too late or miss entire swaths of mobile users (Cobb et al, 2014; Tan et al, 2020). Furthermore, numerous critical studies of communication technologies have focused on how applications like Google and Facebook monitor users’ activity to capitalize on fleeting seconds of their attention to predict their future desires and consumption patterns (McChesney, 2001; Noble, 2018; Vaidhyanathan, 2018; Wu, 2016; Zuboff, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of warning apps revealed that malfunctions and the temporal and spatial relevance of warnings are main concerns [30]. Furthermore, dependability, avoidance of advertisement, resource efficiency, appropriate audio interface for alerting, and avoidance of in-app browsing are usability requirements that are particular to warning apps [52]. Research suggests that even during the COVID-19 crisis, pandemics were infrequently mentioned as hazards that should be included in a multi-hazard warning app [12].…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…App store reviews, which contain bug reports, feature strengths or shortcomings, user requests, praise, complaints, and/or usage scenarios [19] have been successfully used to gain insights into warning app usability issues [30,52]. Written by users who are specifically motivated to share their experiences, as a crowdsourced task to identify the best app for a specific purpose [29] or to increase pressure on the developers [40], they are not necessarily representative of the average app's user.…”
Section: Introduction and Related Workmentioning
confidence: 99%